High-valence cation modified polycrystalline O3 type sodium ion battery layered positive electrode material and preparation method thereof

By doping the positive electrode material of polycrystalline O3 type NaNi1/3Fe1/3Mn1/3O2 layered sodium ion battery with high valence niobium ion, the problem of poor cyclic stability during the charging and discharge process is solved, and the structural stability and electrochemical performance are improved.

CN119674058AActive Publication Date: 2025-03-21CENT SOUTH UNIV
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411936918.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-21
Estimated Expiration
2044-12-26

AI Technical Summary

Technical Problem

The existing polycrystalline O3 type NaNi1/3Fe1/3Mn1/3O2 layered positive electrode material has a problem of poor cycle stability during charging and discharging, especially when the charging cutoff potential exceeds 4.0 V, the capacity rapidly decays and poor cycle stability.

Method used

By doping the positive electrode material of polycrystalline O3 type NaNi1/3Fe1/3Mn1/3O2 layered sodium ion battery with high-valent niobium ion doping, Na(Ni1/3Fe1/3Mn1/3)1-xNbxO2 (0 < x ≤ 0.1) material was prepared to inhibit the phase change of the material during charge and discharge, and improve structural stability.

Benefits of technology

By doping Nb5+, the orderly arrangement in the transition metal layer of the layered material is destroyed, the orderly transition of Na+/vacancies is disrupted, the diffusion energy barrier of Na+ is reduced, the structural stability and electrochemical performance of the material are improved, and the cycle stability and capacity retention rate are significantly improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119674058A_ABST
    Figure CN119674058A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of sodium-ion batteries, and relates to a high-valence cation modified polycrystalline O3 type sodium-ion battery layered positive electrode material and a preparation method thereof. The molecular formula of the battery positive electrode material is Na (Ni < 1 / 3 > Fe < 1 / 3 > Mn < 1 / 3 >) < 1-x > Nb < x > O < 2 >, x is greater than or equal to 0.1 and less than or equal to 0.1, in the battery positive electrode material, the mesoscopic and / or macroscopic morphology is spherical secondary particles, and the spherical secondary particles are composed of lamellar primary particles. The preparation method comprises the following steps: setting a molar ratio, grinding and uniformly mixing a polycrystalline raw material, a sodium source and a niobium source to obtain mixed powder; the mixed powder is subjected to heat preservation for 4-8 h at the temperature of 400-600 DEG C and then subjected to heat preservation for 10-20 h at the temperature of 850-950 DEG C; the composition is reasonable in design, the preparation process is simple and controllable, and the obtained product is excellent in performance and convenient for industrial application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of sodium ion batteries and relates to a high-valent cation-modified polycrystalline O3 sodium ion battery layered positive electrode material and a preparation method thereof. Background Art

[0002] With the rapid development of mobile electronic devices and the electric vehicle industry, the consumption of lithium-ion batteries has increased rapidly, resulting in an increasingly prominent problem of insufficient lithium resources and a rapid rise in lithium prices. The high price of lithium-ion batteries has seriously hindered their application in large-scale energy storage fields that have high requirements for battery prices. In contrast, sodium resources are abundant and have huge price advantages, which can well solve the problem of insufficient lithium resources. Sodium and lithium have similar physical and chemical properties, and their mature research methods and process technologies can be fully learned. Therefore, sodium-ion batteries, with their unique cost advantages, are considered to be the most promising energy storage devices to replace lithium-ion batteries for large-scale energy storage systems.

[0003] Layered transition metal oxides are considered the most promising cathode materials for sodium-ion batteries due to their abundant sources, environmental friendliness, simple preparation, and excellent electrochemical performance. Compared with the Na-poor P2 phase, the Na-rich O3 phase layered oxides have a higher sodium content and thus a higher specific capacity in the full battery, indicating their superior commercialization potential. According to recent research results, O3-type NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2(NFM) is considered as a promising commercial cathode for SIBs due to its relatively high theoretical capacity and cycling stability. + During the extraction / insertion process, the NFM cathode material undergoes a continuous phase transition from O3hex. - P3hex. - O3′mon. - P3′mon. + During the extraction process, when the charge cut-off potential exceeds 4.0 V, the capacity decays rapidly and the cycle stability is poor.

[0004] Sodium ion layered oxides mainly have two morphologies: single crystal and polycrystalline. Currently, there are few reports on how to obtain high-performance polycrystalline sodium ion layered positive electrode materials. Summary of the invention

[0005] In order to solve the problems existing in the prior art, the present invention aims to provide a high-valent cation-modified O3-type sodium ion battery layered positive electrode material and a preparation method thereof, by modifying polycrystalline O3-type NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3Specific high-valence niobium ion doping in the O2 layered sodium-ion battery cathode can inhibit the phase transition that occurs during charge and discharge of the material, disrupt the Na + / vacancy order, thereby improving the structural stability and further enhancing its electrochemical performance.

[0006] The technical solution adopted in the present invention is: A polycrystalline O3-type layered sodium-ion battery cathode material, wherein the sodium-ion battery cathode material is a polycrystalline O3-type layered sodium-ion battery cathode material with the molecular formula Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-x Nb x O2, where 0 < x ≤ 0.1. In the polycrystalline O3-type layered sodium-ion battery cathode material, the mesoscopic and / or macroscopic morphology is spherical secondary particles, and the spherical secondary particles are composed of lamellar primary particles.

[0007] Preferably, the value of x is 0.005 - 0.03.

[0008] As a further preference, the value of x is 0.005 - 0.025.

[0009] As an even further preference, the value of x is 0.015 - 0.025, which of course includes the parameter range of 0.019 - 0.021 and parameters such as 0.02.

[0010] Preferably, the particle size of a single secondary particle is 1 - 5 microns, preferably 1 - 2 microns.

[0011] The preparation method of a polycrystalline O3-type layered sodium-ion battery cathode material of the present invention includes the following steps: (1) According to the set molar ratio in the molecular formula, grind and mix the polycrystalline raw material with a sodium source and a niobium source evenly to obtain a mixed powder; the polycrystalline raw material is polycrystalline (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )CO3; (2) Keep the mixed powder at 400 - 600 °C for 4 - 8 h first, and then keep it at 850 - 950 °C for 10 - 20 h to obtain the O3-type layered sodium-ion battery cathode material.

[0012] Preferably, in step (1), the sodium source is sodium acetate, sodium nitrate or sodium carbonate; the niobium source is an oxide of niobium.

[0013] Preferably, the particle size of the polycrystalline raw material is less than or equal to 20 microns, preferably 1 - 10 microns.

[0014] Preferably, the polycrystalline (Ni1 / 3 Fe 1 / 3 Mn 1 / 3 )CO3 precursor, the specific steps are as follows: NiSO4, FeSO4, and MnSO4 are dissolved in deionized water at a stoichiometric ratio of 1:1:1 to prepare a solution A with a volume of 1L and a metal ion concentration of 2 mol / L, and then prepare a solution B with a Na2CO3 concentration of 2 mol / L and a NH3·H2O concentration of 0.24 mol / L. A peristaltic pump is used to simultaneously inject solutions A and B into a 5L reaction vessel containing 1L of deionized water at a feeding rate of 1.5 mL / min. The pH value in the reactor is controlled between 7.75-7.85 by adjusting the flow rate of the solution, and the temperature of the reactor is 55 ℃. When solution A or B is dripped, the reaction product is taken out, and the residual impurities are removed by washing and filtering with deionized water for multiple times, and then transferred to a vacuum oven, heated to 120 ℃, and dried for 24 hours to obtain polycrystalline (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )CO3 precursor. Of course, commercially available polycrystalline (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )CO3 precursors can also be used in the present invention.

[0015] Preferably, the particle size of the sodium source is less than or equal to 150 microns, preferably 50-100 microns.

[0016] Preferably, the particle size of the niobium source is 200-500 nanometers.

[0017] Preferably, in step (2), the oxidizing atmosphere is an air atmosphere or an oxygen atmosphere.

[0018] Preferably, in step (2), the mixed powder is first heated from room temperature to 400-600°C at a heating rate of 1-2°C / min and kept at that temperature for 4-8 h, and then heated to 850-950°C at a heating rate of 3-8°C / min and kept at that temperature for 10-20 h.

[0019] After optimization, the obtained product of the present invention is assembled into a CR2016 button battery, and the capacity retention rate of the battery is greater than or equal to 80% after 200 cycles at 1C, and greater than or equal to 85% after further optimization.

[0020] After optimization, the obtained product of the present invention is assembled into a CR2016 button battery. The capacity retention rate of the battery after 100 cycles at 1C is greater than or equal to 90.5%, and after further optimization is greater than or equal to 92.5%, which is significantly higher than the prior art.

[0021] Principle of the Invention For the existing polycrystalline O3 type NaNi 1 / 3 Fe1 / 3 Mn 1 / 3 O2 layered positive electrode materials have the disadvantage of poor cycle stability. The present invention adopts Nb 5+ The introduction of can destroy the orderly arrangement of metal ions in the transition metal layer of the layered material, thereby inhibiting the Na + and vacancies, reducing the Na + The diffusion barrier of Nb 5+ In order to maintain electrical neutrality, some Ni 3+ It will be reduced, thus it can act as a stabilizer to reduce the structural distortion and slip of layered materials during the charge and discharge process and enhance the structural stability. Compared with single crystal structures, the preparation of polycrystalline layered oxides is usually cheaper and easier to mass produce. In addition, polycrystalline layered oxides can provide higher specific capacity to meet the needs of high energy density applications. Polycrystalline layered oxides also have advantages in rate performance. By modifying their microstructure through doping, the structural stability of the material can be effectively improved and the cycle life can be enhanced.

[0022] Beneficial Effects (1) After element doping, the prepared material remains in pure O3 phase and does not change the structural characteristics of the original material.

[0023] (2) The prepared material can effectively inhibit the complex phase transitions that occur in polycrystalline O3-type layered materials during the charge and discharge process, thereby improving the structural stability and thereby improving the electrochemical performance of the material.

[0024] (3) The introduction of Nb destroys the orderly arrangement of the transition metal layers in the layered material, thereby disrupting the Na + / Vacancy ordering, reducing Na + Diffusion barrier, improving the rate performance of the material.

[0025] (4) The preparation method provided by the present invention is simple, the conditions are easy to control, and it is convenient for industrialization. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 is an electron scanning microscopic image of the positive electrode materials obtained in Example 1 and Comparative Example 1; Figure 2 1C cycle performance diagram of the positive electrode materials obtained in Example 1 and Comparative Example 1; Figure 3 is the X-ray diffraction pattern of the positive electrode materials obtained in Example 2 and Example 1; Figure 4 is an electron scanning microscopic image of the positive electrode materials obtained in Example 2 and Example 1; Figure 5 1C cycle performance diagram of the positive electrode materials obtained in Example 2 and Example 1; Figure 6 This is a rate test diagram of the positive electrode materials obtained in Example 2 and Example 1; Figure 7 is the X-ray diffraction pattern of the positive electrode material obtained in Example 3; Figure 8 is a cycle performance diagram of the positive electrode material obtained in Example 3 at 1C; Fig. 9 is the X-ray diffraction pattern of the positive electrode material obtained in Example 4; Fig.10 is a cycle performance diagram of the positive electrode material obtained in Example 4 at 1C; Fig.11 is the X-ray diffraction pattern of the positive electrode material obtained in Example 5; Fig.12 is a cycle performance diagram of the positive electrode material obtained in Example 5 at 1C; Fig.13 It is a diagram of the particle size of positive electrode materials with different Nb doping amounts in the embodiments and comparative examples. DETAILED DESCRIPTION

[0027] Example 1

[0028] Polycrystalline NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 Preparation of O2: The steps are: Weigh 1.8098 g polycrystalline (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )CO3 powder (particle size of 1-10 microns, commercially available) and 1.1185 gNa2CO3 (particle size of 50 - 100 microns) powder were placed in a mortar and ground thoroughly, then stirred evenly at a stirring speed of 500 r / min. The evenly mixed powder was transferred to a muffle furnace and heated to 450°C at a heating rate of 1°C / min, kept warm for 6 h, and then heated to 900°C at a heating rate of 5°C / min and kept warm for 20 h. After cooling to room temperature with the furnace, the polycrystalline O3-type layered oxide sodium positive electrode material NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2, after grinding, the particle size of the material is controlled between 1-2 microns.

[0029] Electrochemical performance determination: Using NMP as the medium, the NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3O2, acetylene black and PVDF were mixed in a mass ratio of 8:1:1 to form a slurry, which was evenly coated on an aluminum foil and cut into positive electrode sheets with a diameter of 12 mm after drying. Sodium metal foil was used as the negative electrode, glass fiber GF / D was used as the separator, and 1M NaPF6 PC / FEC (volume ratio of 95:5) solution was used as the electrolyte. CR2016 button batteries were assembled in an argon-filled glove box.

[0030] Comparative Example 1 Same as Example 1, except that single crystal (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )CO3 powder (particle size is 1-5 microns), the obtained material is single crystal O3 type NaNi 1 / 3 Fe 1 / 3 Mn 1 / 3 O2 layered cathode material.

[0031] The batteries assembled in Example 1 and Comparative Example 1 were subjected to charge and discharge cycle tests in a Xinwei battery testing system under the same test conditions, with a voltage range of 2 to 4.0 V and a test temperature of 30°C.

[0032] like Figure 1 Shown are scanning electron micrographs of Example 1 and Comparative Example 1. It can be seen from the figure that the two present different morphologies. Example 1 is a spherical secondary particle composed of lamellar primary particles, while Comparative Example 1 exhibits a large single crystal.

[0033] like Figure 2 As shown, the cycle performance test results of Example 1 and Comparative Example 1, the initial capacity of the battery of Comparative Example 1 is slightly higher, but the capacity retention rate after 200 cycles at 1C is only 62.45%, while the capacity retention rate of the battery of Example 1 is increased to 67.19% after 200 cycles at 1C, and the cycle performance is significantly improved.

[0034] Example 2 Polycrystalline Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-x Nb x Preparation of O2 (x = 0.02, in molar ratio): The steps are: Same as Example 1, except that the Nb doping amount of the positive electrode material is 2%, and the prepared positive electrode material is polycrystalline Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.98 Nb 0.02 O2. Specifically: weigh 1.7736 g polycrystalline (Ni 1 / 3 Fe1 / 3 Mn 1 / 3 )CO3 powder (particle size of 1-10 microns), 1.1185 g Na2CO3 powder (particle size of 50-100 microns), 0.0537 g niobium pentoxide (particle size of 200-500 nanometers), put them in a mortar and grind them thoroughly, then stir them evenly at a stirring speed of 500r / min. The mixed powders are transferred to a muffle furnace and heated to 450°C at a heating rate of 1°C / min, kept warm for 6 hours, and then heated to 900°C at a heating rate of 5°C / min and kept warm for 20 hours. After cooling to room temperature with the furnace, polycrystalline Na(Ni 1 / 3 Fe 1 / 3Mn 1 / 3 ) 0.98 Nb 0.02 O2.

[0035] like Figure 3 , which are the X-ray diffraction patterns of the positive electrode materials of Example 2 and Example 1, prove that the doping of Nb does not change the original structural characteristics.

[0036] like Figure 4 As shown, it is the scanning electron micrograph of Example 2 and Example 1. It can be seen from the figure that both are spherical secondary particles composed of lamellar primary particles, which proves that the doping of Nb does not change the original morphology.

[0037] like Figure 5 As shown in the figure, the cycle performance test results of Example 2 and Example 1, the initial capacity of the battery of Example 1 is slightly higher, but the capacity retention rate after 200 cycles at 1C is only 67.19%, while the capacity retention rate of the battery of Example 2 is increased to 92.81% after 100 cycles at 1C, and the capacity retention rate of the battery of Example 2 is increased to 85.55% after 200 cycles at 1C, and the cycle performance is significantly improved.

[0038] like Figure 6 As shown, the results show that the capacity of Example 2 under different rate test conditions is also significantly better than that of Example 1.

[0039] Example 3 Same as Example 1, except that the Nb doping amount of the positive electrode material is 3% (by molar ratio), and the prepared positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.97 Nb 0.03 O2.

[0040] like Figure 7As shown, the XRD spectrum of Example 3 shows that the positive electrode material obtained in Example 3 is still in the O3 phase, but due to the increase in the niobium doping amount, the Na3NbO4 impurity phase appears.

[0041] like Figure 8 The figure shows the cycle performance test results of Example 3. Compared with Example 1, the capacity retention rate of Example 3 is improved to 81.35%, which is similar to Example 2. After 100 cycles at 1C, the capacity retention rate of the battery in Example 3 is increased to 90.72%.

[0042] The reason for this is that the capacity is reduced compared to Example 2, possibly due to an increase in the doping amount and the doping element being an electrochemically inactive element.

[0043] Example 4 Same as Example 1, except that the Nb doping amount of the positive electrode material is 0.5% (by molar ratio), and the prepared positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.995 Nb 0.005 O2.

[0044] like Fig. 9 As shown, the XRD spectrum shows that the positive electrode material obtained in Example 4 is still in the O3 phase.

[0045] like Fig.10 , which is the cycle performance test result of Example 4. Compared with Example 1, the capacity retention rate of Example 4 is improved to 71.86%.

[0046] Example 5 Same as Example 1, except that the Nb doping amount of the positive electrode material is 0.1% (by molar ratio), and the prepared positive electrode material is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 0.99 Nb 0.01 O2.

[0047] like Fig.11 As shown, the XRD spectrum of Example 5 shows that the positive electrode material obtained in Example 5 is still in the O3 phase.

[0048] like Fig.12 , which is the cycle performance test result of Example 5. Compared with Example 1, the capacity retention rate of Example 5 is improved to 76.95%.

[0049] like Fig.13 As shown in the figure, the particle size diagram of the positive electrode material with different Nb doping amounts. As the Nb doping amount increases, D50 It decreases gradually, and it can be inferred that the introduction of Nb can play a role in grain refinement.

Claims

1. A polycrystalline O3-type layered sodium ion battery positive electrode material, characterized in that: The positive electrode material of the sodium-ion battery is a polycrystalline O3-type layered positive electrode material for sodium-ion batteries, and its molecular formula is Na(Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 ) 1-x Nb x O2, where 0 < x ≤ 0.

1. In the polycrystalline O3-type layered positive electrode material for sodium-ion batteries, the mesoscopic and / or macroscopic morphology is spherical secondary particles, and the spherical secondary particles are composed of lamellar primary particles.

2. The polycrystalline O3-type layered sodium ion battery positive electrode material according to claim 1, characterized in that: The value of x is 0.005~0.

03.

3. The polycrystalline O3-type layered sodium ion battery positive electrode material according to claim 1, characterized in that: The value of x is 0.005~0.

025.

4. The polycrystalline O3-type layered sodium ion battery positive electrode material according to claim 1, characterized in that: The value of x is 0.015~0.

025.

5. The polycrystalline O3 type layered sodium ion battery positive electrode material according to claim 1, characterized in that: The particle size of a single secondary particle is 1-5 microns, preferably 1-2 microns.

6. A method for preparing a polycrystalline O3-type layered sodium ion battery positive electrode material according to any one of claims 1 to 5, characterized in that: The steps include: (1) According to the molar ratio set in the molecular formula, the polycrystalline raw material, the sodium source and the niobium source are ground and mixed to obtain a mixed powder; the polycrystalline raw material is polycrystalline (Ni 1 / 3 Fe 1 / 3 Mn 1 / 3 )CO3; (2) The mixed powder is first kept at 400-600 °C for 4-8 h, and then kept at 850-950 °C for 10-20 h to obtain an O3-type layered sodium ion battery positive electrode material.

7. The polycrystalline O3-type layered sodium ion battery positive electrode material according to claim 6, characterized in that: In step (1), the sodium source is sodium acetate, sodium nitrate or sodium carbonate; and the niobium source is niobium oxide.

8. The polycrystalline O3-type layered sodium ion battery positive electrode material according to claim 6, characterized in that: The particle size of the polycrystalline raw material is less than or equal to 20 microns, preferably 1-10 microns; The particle size of the sodium source is less than or equal to 150 microns, preferably 50-100 microns; The particle size of the niobium source is 200 - 500 nanometers.

9. The polycrystalline O3-type layered sodium ion battery positive electrode material according to claim 6, characterized in that: In step (2), the oxidizing atmosphere is an air atmosphere or an oxygen atmosphere.

10. The polycrystalline O3-type layered sodium ion battery positive electrode material according to claim 6, characterized in that: In step (2), the mixed powder is first heated from room temperature to 400-600°C at a heating rate of 1-2°C / min and kept at that temperature for 4-8 h, and then heated to 850-950°C at a heating rate of 3-8°C / min and kept at that temperature for 10-20 h.

Citation Information

Patent Citations

  • Super-high valence metal ion modified sodium ferronickel manganate positive electrode material and preparation method thereof

    CN116504950A

  • Sodium-ion battery positive electrode material and synthesis method thereof

    CN116960311A

  • Sodium-ion battery positive electrode material with low residual alkali, preparation method and sodium-ion battery

    CN116986649A

  • Multi-element polycrystal positive electrode material for high-rate lithium or sodium battery and preparation method of multi-element polycrystal positive electrode material

    CN117185364A

  • Preparation method and application of layered oxide positive electrode material

    CN117963999A